Utilisation of controlled pore topology for the separation of bioparticles in a mixed-glass beads column - Mota, M. (2006)
To study the flow of shaped particles in porous media, elution of spherical and rod-like micro-organisms was performed through beds of spherical glass beads. A 0.04 cm/s constant flow rate was used with 5 μm yeast suspensions, 1 μm latex micro-spheres and rod-like bacilli Lactobacillus bulgaricus 6 μm long and 0.5 μm in diameter. Yeast cells’ diameter is close to the bacilli length and micro-spheres have the same diameter as bacilli. All particle types have similar density. To make the different packing beds, 1.125 mm coarse beads and 0.1115 mm fine beads were used. Experiments were carried out using a column loaded with the binary packing (volume fraction of coarse particles in the mixture 0.7) or a monosize packing with the same amount of coarse or fine particles as used in the binary packing. Analysis of experimental results was based on two models: pure exclusion effect and hydrodynamic separation model [hydrodynamic chromatography (HDC)]. Results for spheres show that the classic HDC model fits to the experimental data whenever the ratio of particle size to the pathway bend scale is high (1/100, micro-spheres). However, if this ratio increases and becomes 1/20, the HDC model needs to be corrected due to the effect of channel wall curvature on exclusion. This led to a modified HDC equation of the form R = B/(1 + 2λ − 2.8λ2), where R is the retention, λ is the aspect ratio and constant B ≥ 1. Bacillus separation follows an exclusion mechanism, since pore topology is important in the separation of shaped particles when the aspect ratio approaches λ = 0.1. In the case of a binary packing bed, rod-like particles display a different behaviour than the one exhibited by the spherical particles of the same scale as bacilli, either in length or in diameter. This may be explained by the interaction between rod-like bacilli and the bed's pore topology. A generalised exclusion model for particles was proposed to be R = A/(1 − λ)z, where A is the coefficient proportional to the tortuosity and the parameter z = 1, 2 or 3 depends mainly on pore shape. Controlled pore topology opens interesting applications for bio-separation (in porous micro-fluidic devices, deep bed filtration) and might be especially important for macromolecules and micro-organisms separation with different shapes.